2014
DOI: 10.1007/978-3-319-10404-1_72
|View full text |Cite
|
Sign up to set email alerts
|

fhSPECT-US Guided Needle Biopsy of Sentinel Lymph Nodes in the Axilla: Is it Feasible?

Abstract: Until now, core needle biopsy of the axillary sentinel lymph nodes in early stage breast cancer patients is not possible, due to the lack of a proper combination of functional and anatomical information. In this work we present the first fully 3D freehand SPECT -ultrasound fusion, combining the advantages of both modalities. By using spatial positioning either with optical or with electromagnetic tracking for the ultrasound probe, and a mini gamma camera as radiation detector for freehand SPECT reconstructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Recently, it has been shown that freehand SPECT-USguided needle biopsy of sentinel lymph nodes in the axilla is feasible. 26 In the present study, we present the first results of free- hand SPECT-USgFNAC in 6 patients with early-stage head and neck cancer. Limitations of this study are the small number of patients included and the lack of pathologically positive freehand SPECT-USgFNAC findings, but the concept and feasibility of sentinel node identification and aspiration by freehand SPECT-USgFNAC are shown.…”
mentioning
confidence: 92%
“…Recently, it has been shown that freehand SPECT-USguided needle biopsy of sentinel lymph nodes in the axilla is feasible. 26 In the present study, we present the first results of free- hand SPECT-USgFNAC in 6 patients with early-stage head and neck cancer. Limitations of this study are the small number of patients included and the lack of pathologically positive freehand SPECT-USgFNAC findings, but the concept and feasibility of sentinel node identification and aspiration by freehand SPECT-USgFNAC are shown.…”
mentioning
confidence: 92%
“…A new technique fusing freehand single-photon emission computed tomography with realtime ultrasound has been described to identify axillary SLNs in breast cancer patients that could improve PNB/ SLN concordance. 17 In this proof of concept study, we demonstrate that PNB of the SLN is technically feasible utilizing existing modalities available to facilities performing standard dual tracer SLND with Tc 99 sulfur colloid, isosulfan blue dye, and typical ultrasound equipment. With advances in the molecular profiling of primary tumor tissue and ongoing studies questioning the need to remove known axillary disease in the setting of adjuvant systemic and radiation therapy and even after neoadjuvant systemic therapy, axillary surgery currently affords more prognostic rather than therapeutic significance.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary of [5] and [4], the presented solution provides real-time simultaneous multi-modal nuclear and US imaging, without requiring for consecutive imaging and the need to correct for deformations due to the US acquisition. The use of the camera-in-hand inside-out tracking voids the necessity for an external optical tracking system, relieving the operator from having to pay attention to not obstructing the line of sight.…”
Section: Discussionmentioning
confidence: 97%
“…Since these techniques provide functional information only, open surgery is required for the removal of sLNs. The possibility of punch biopsy under multi-modal guidance was recently introduced by combining freehand SPECT with 3D compounded ultrasound [4] and extended to thyroid imaging [5]. The current approach, whilst allowing for a combination of nuclear and anatomical information, suffers from having to conduct two subsequent acquisitions.…”
Section: Introductionmentioning
confidence: 99%